Elevated cerebrospinal fluid 5-hydroxyindoleacetic acid in macaques following early life stress and inverse association with hippocampal volume: preliminary implications for serotonin-related function in mood and anxiety disorders - Coplan, Jeremy D.; Fulton, Sasha L.; Reiner, Wade; Jackowski, Andrea; Panthangi, Venkatesh; Perera, Tarique D.; Gorman, Jack M.; Huang, Yung-yu; Tang, Cheuk Y.; Hof, Patrick R.; Kaffman, Arie; Dwork, Andrew J.; et al. (Frontiers in Behavioral Neuroscience, 2014)
Background: Early life stress (ELS) is cited as a risk for mood and anxiety disorders, potentially through altered serotonin neurotransmission. We examined the effects of ELS, utilizing the variable foraging demand (VFD) macaque model, on adolescent monoamine metabolites. We sought to replicate an increase in cerebrospinal fluid (CSF) 5-hydroxyindoleacetic acid (5-HIAA) observed in two previous VFD cohorts. We hypothesized that elevated cisternal 5-HIAA was associated with reduced neurotrophic effects , conceivably due to excessive negative feedback at somatodendritic 5-HT1A autoreceptors. A putatively decreased serotonin neurotransmission would be reflected by reductions in hippocampal volume and white matter (WM) fractional anisotropy (FA). Methods: When infants were 2-6 months of age, bonnet macaque mothers were exposed to VFD. We employed cisternal CSF taps to measure monoamine metabolites in VFD (N = 22) and non-VFD (N = 14) offspring (mean age = 2.61 years). Metabolites were correlated with hippocampal volume obtained by MRI and WM FA by diffusion tensor imaging in young adulthood in 17 males [10 VFD (mean age = 4.57 years)]. Results: VFD subjects exhibited increased CSF 5-HIAA compared to non-VFD controls. An inverse correlation between right hippocampal volume and 5-HIAA was noted in VFD- but not controls. CSF HVA and MHPG correlated inversely with hippocampal volume only in VFD. CSF 5-HIAA correlated inversely with FA of the WM tracts of the anterior limb of the internal capsule (ALIC) only in VFD. Conclusions: Elevated cisternal 5-HIAA in VFD may reflect increased dorsal raphe serotonin, potentially inducing excessive autoreceptor activation, inducing a putative serotonin deficit in terminal fields. Resultant reductions in neurotrophic activity are reflected by smaller right hippocampal volume. Convergent evidence of reduced neurotrophic activity in association with high CSF 5-HIAA in VFD was reflected by reduced FA of the ALIC.